Combined exercise training in asymptomatic elderly with controlled hypertension: Effects on functional capacity and cardiac diastolic function - Guirado, Gabriel N. [UNESP]; Damatto, Ricardo L. [UNESP]; Matsubara, Beatriz B. [UNESP]; Roscani, Meliza G. [UNESP]; Fusco, Danieliso R. [UNESP]; Cicchetto, Luiz A.F. [UNESP]; Seki, Marcos M. [UNESP]; Teixeira, Altamir S. [UNESP]; Valle, Adriana P. [UNESP]; Okoshi, Katashi [UNESP]; Okoshi, Marina P. [UNESP] (International Scientific Information, 2012)
Background: Aging is associated with changes in cardiac structure and function that are associated with left ventricular diastolic dysfunction. Whether diastolic functional alterations during senescence are manifestations of the intrinsic aging process or related to cardiac adaptations to a more sedentary lifestyle is still unsettled. This was a prospective study evaluating the effects of a 6-month combined exercise training period on functional capacity and diastolic function in sedentary elderly patients with controlled arterial hypertension. Material/Methods: Functional capacity was assessed by exercise stress test and muscle strength was evaluated by the one-repetition maximum test. Cardiac structures and function were analyzed by transthoracic echocardiography. Results: Fifteen patients, 68±8 years old, completed the training program. Exercise training significantly improved physical capacity (distance walked: 551±92 vs. 630±153 m, P<0.05; work load: 7.2±1.7 vs. 8.5±3.0 METs, P<0.05) and upper and lower extremity muscle strength (P<0.001). Arterial blood pressure significantly decreased after training (systolic blood pressure: 134±9 vs. 128±8 mmHg; diastolic blood pressure: 82±7 vs. 77±6 mmHg; P<0.05). Cardiac structures and left and right systolic and diastolic function did not change after combined training (P>0.05). Conclusions: Combined and supervised training for a 6-month period increases physical capacity and muscle strength in elderly patients with controlled arterial hypertension without changing resting left ventricular diastolic function. © Med Sci Monit.
Keywords: Aging; Arterial hypertension; Diastolic function; Echocardiogram; Exercise; Functional capacitycr